Analysis of the impact of selected user interface elements on its usability - Wojtal, Damian; Powroźnik, Paweł (Journal of Computer Sciences Institute, 2025)
The aim of the study was to examine which user interface elements attract the most user attention. The evaluation was conducted using the eye-tracking technique. The analysis included comparisons based on average task completion time, the number of fixations, the percentage of correctly completed tasks, scan paths, and heatmaps. The obtained results confirmed the thesis that selected user interface elements, such as button layout, color scheme, and information placement, significantly influence usability, with proper arrangement of key elements improving interaction efficiency. Furthermore, the analysis confirmed most of the hypotheses, highlighting the importance of precise interface design.